2012
DOI: 10.4103/1596-3519.102852
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diarrhea disease and risk factors in Jos University Teaching Hospital, Nigeria

Abstract: Our study demonstrated an important relationship between diarrheal morbidity and low maternal education, nonexclusively breastfed infant, and previous diarrheal episode in a sibling. It thus meant that diarrhea morbidity is still an important problem for infants in our environment. Moreover, maternal education and exclusive breastfeeding are still relevant viable measures in curbing diarrhea in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
42
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 9 publications
20
42
3
1
Order By: Relevance
“…Children whose mothers/caretakers had never attended school were 3.7 times and attended primary were 2.9 times more likely to have diarrheal diseases compared to those who attended tertiary level of education. This finding is similar with other studies [6,[18][19][20][21][22]. This was also supported by RDHS in 2014-2015 where it was revealed that the prevalence of diarrhea is higher among children whose mothers have no education (14 percent) or a primary education (12 percent) than among those whose mothers have a secondary education or higher (9 percent).…”
Section: Discussionsupporting
confidence: 82%
“…Children whose mothers/caretakers had never attended school were 3.7 times and attended primary were 2.9 times more likely to have diarrheal diseases compared to those who attended tertiary level of education. This finding is similar with other studies [6,[18][19][20][21][22]. This was also supported by RDHS in 2014-2015 where it was revealed that the prevalence of diarrhea is higher among children whose mothers have no education (14 percent) or a primary education (12 percent) than among those whose mothers have a secondary education or higher (9 percent).…”
Section: Discussionsupporting
confidence: 82%
“…Diarrhoea kills an estimated 2.5 million people each year, with about 60-70% of them being children under five years of age (Cesar et al, 2000). The disease is responsible for over a quarter of the deaths of children in the world today (Yilgwan and Okolo, 2015). Most of these deaths occur in developing countries where an estimated 25% of under-five mortality is directly attributed to diarrhoea disease (Cesar et al, 2000;Yilgwan and Okolo, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The disease is responsible for over a quarter of the deaths of children in the world today (Yilgwan and Okolo, 2015). Most of these deaths occur in developing countries where an estimated 25% of under-five mortality is directly attributed to diarrhoea disease (Cesar et al, 2000;Yilgwan and Okolo, 2015). Ready-to-eat food (RTE) is a potential reservoir of pathogens that transmit diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Childhood diseases including diarrhea account for greater proportion of childhood deaths in Nigeria 2,9 . The incidence of childhood diarrhea is estimated to account for over 160,000 of all deaths in under-five children annually in Nigeria 10 . Diarrheal incidence has been found to be highest in the first two years of life and declines as a child grows older 11 .…”
Section: African Journal Of Reproductive Health September 2017; 21 (3mentioning
confidence: 99%